Identification of Chloride Channels CLCN3 and CLCN5 Mediating the Excitatory Cl− Currents Activated by Sphingosine-1-Phosphate in Sensory Neurons - Qi, Yanmei; Mair, Norbert; Kummer, Kai K.; Leitner, Michael G.; Camprubí-Robles, María; Langeslag, Michiel; Kress, Michaela (Frontiers in Molecular Neuroscience, 2018)
Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid involved in numerous physiological and pathophysiological processes. We have previously reported a S1P-induced nocifensive response in mice by excitation of sensory neurons via activation of an excitatory chloride current. The underlying molecular mechanism for the S1P-induced chloride conductance remains elusive. In the present study, we identified two CLCN voltage-gated chloride channels, CLCN3 and CLCN5, which mediated a S1P-induced excitatory Cl- current in sensory neurons by combining RNA-seq, adenovirus-based gene silencing and whole-cell electrophysiological voltage-clamp recordings. Downregulation of CLCN3 and CLCN5 channels by adenovirus-mediated delivery of shRNA dramatically reduced S1P-induced Cl- current and membrane depolarization in sensory neurons. The mechanism of S1P-induced activation of the chloride current involved Rho GTPase but not Rho-associated protein kinase. Although S1P-induced potentiation of TRPV1-mediated ionic currents also involved Rho-dependent process, the lack of correlation of the S1P-activated Cl- current and the potentiation of TRPV1 by S1P suggests that CLCN3 and CLCN5 are necessary components for S1P-induced excitatory Cl- currents but not for the amplification of TRPV1-mediated currents in sensory neurons. This study provides a novel mechanistic insight into the importance of bioactive sphingolipids in nociception.